2014
DOI: 10.2209/tdcpublication.55.125
|View full text |Cite
|
Sign up to set email alerts
|

Cohort Study on Incidence of Coronal and Root Caries in Japanese Adults

Abstract: The purpose of this study was to investigate the incidence of coronal and root caries in participants aged 20-59 years in Japan. The participants comprised 118 men and 23 women undergoing a re-examination 5 years after an initial examination. Lesions were classified as gingival recession, decayed root caries, or filled surfaces. The rates of incidence of coronal caries over the 5 years were 87% in women aged 20-29 years, 77% in men aged 20-29 years, 62% in men aged 30-39 years, 64% in men aged 40-49 years, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…[ 20 ] Likewise, studies by Sugihara et al . [ 21 ] reported a significant increase in the prevalence of root caries with increasing age among Japanese population ( P = 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 ] Likewise, studies by Sugihara et al . [ 21 ] reported a significant increase in the prevalence of root caries with increasing age among Japanese population ( P = 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these methodological issues new studies are available to be included in a contemporary meta-analysis (14,15).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Silva et al [11] found a significantly higher incidence of root caries in Australian nursing home residents aged above 85 years than in those below that age. Older age [20] and male sex [8] were also identified as risk factors for root caries incidence among community-dwelling older people.…”
Section: Discussionmentioning
confidence: 99%